KH. HADERANIE HN DAN GAGASANNYA DI BIDANG TASAWUF - Zainab Hartati (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
K.H. Haderanie HN is foremost Muslim scholar from the Central Kalimantan Province, he was born in Puruk Cahu, Murung Raya. He is known as the leading figure of the religious person who is respected by various religious figures (Islam, Christian, Hindu, Buddha and Kaharingan). The charismatic muslim scholar not only as the Islam religious figure (as the management in the organisation NU and the MUI, tutor and also a tasawuf and deity/teacher as well as was active in the governments politik and author of some books especially the book of tasawuf knowledge and the deity, his reference is made as material of the tasawuf teaching and the deity inside and overseas, he got the degree of honour as the Doctor of Honoris Causa (HC), because of his writing, various of the religious figures and the senior officials in Central Kalimantan often ask for his advice and blessing to him.